Executive summary of the KDIGO 2022 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease: an update based on rapidly emerging new evidence - Rossing, Peter; Caramori, M. Luiza; Chan, Juliana C.N.; al., et (KIDNEYS, 2023)
No abstract